Towards a fault model for BDI agents: an initial study - Cunha, Francisco J. P.; Cirilo, Elder; Lucena, Carlos (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Given the growing approaches based on the paradigm of multi-agent systems and hence the need to maintain the quality of the software produced, testing becomes an activity of a great importance. For the agent-oriented projects in the BDI architecture is not different. Thus, it is necessary for testing agents to have a suitable fault model that ensure the correctness of the proposed behavior. In this paper, we propose an initial analysis of a fault model. The structure of plans and goals of the agents is transformed into a sequence of actions in order to allow its verification and execution control.